Prática de atividade física e pressão arterial em adolescentes: uma análise longitudinal - Prazeres Filho, Alcides (2021)
The relationship between the time of moderate to vigorous physical activity practice and blood pressure in adolescents remains inconclusive, especially when considering the form of accumulation of this time (total and bout times), the dose response relationship and the possible role moderator of nutritional status, which is one of the main risk factors for high blood pressure. This study aimed to analyze the influence of total and bout times of moderate physical activity (MPA), vigorous (VPA) and moderate to vigorous (MVPA) and the performance of MVPA doses on the blood pressure of adolescents. A longitudinal observational study, which used data from 138 adolescents (53.6% female), aged 10 to 13 years in the base year, submitted to the use of an accelerometer in the four years of collection (2014 to 2017) of the LONCAAFS Study – Longitudinal Study on Sedentary Behavior, Physical Activity, Diet and Adolescent Health. Were used an Actigraph to measured AFM, AFV and AFMV and bout times <5, <10, >5 and >10 minutes of each PA intensity (minutes/day). In addition, were created MVPA doses (>15 and >30 minutes/day) from the total times and in bouts, classifying the adolescents into two groups: those who met the MVPA dose (>15 or >30 minutes/day) in two or more years vs. those who did not attend or attend in less than two years. Systolic (SBP) and diastolic (DBP) blood pressure were measured by an automatic Omron HEM – 7200 brand monitor. Generalized Estimating Equation (GEE) analysis was used to associate PA practice indicators with SBP and DBP, considering the nutritional status as a moderator. The times total and in bouts of <5 and <10 minutes of AFM and bouts of <5 and <10 minutes of MVPA were associated with lower mean values of SBP and DBP in female adolescents. In overweight/obese adolescents, MPA, VPA and MVPA accumulated in bouts <5 and <10 minutes were inversely associated with SBP and DBP, and VPA time in bouts >5 minutes with DBP. Exposure to doses >15 minutes/day of MVPA over two or more years was associated with lower SBP and DBP values. No significant interactions (p>0.05) of MVPA doses with sex and nutritional status were observed. The findings of this study indicated that there is an inverse relationship between the practice of PA and BP in adolescents and that female adolescents and those with overweight/obesity accumulated the practice time, even in bouts of less than 10 minutes, and adolescents who remained active over the years in doses of at least 15 minutes per day of MVPA, tended to have lower mean BP values.